Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1080/02705060.2012.667371
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of phytoplankton functional groups and its relationship with the environment in river: a case study in northeast China

Abstract: In this study, the concept of functional groups was applied for the first time to the seasonal dynamics of the phytoplankton community of Mudanjiang River (northeast China). The environmental variables as well as the phytoplankton communities were determined in 2007. The river showed strong seasonal fluctuations in water physical and chemical condition. A total of 11 phytoplankton functional groups (C, D, E, J, MP, P, T, T B , W1, X2 and Y) were identified that included 30 species. Groups C (Asterionella formo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Moreover, the periphyton community, which prefers warm water, exhibited higher relative abundances in spring/summer, such as functional groups B, J, and F (Jiang et al, 2013), whereas functional group D which prefers cold water (Jiang et al, 2013), showed higher proportions of periphyton in winter. Our results, therefore, support the view that functional group can be used as an approach to analyze the seasonal variability in algal community (Yang et al, 2011;Yu et al, 2012). Except for winter, the periphyton functional composition responded strongly to nutrient addition and temperature increase, which is consistent with the responses of periphyton genus composition to nutrient and temperature in spring, summer and winter.…”
Section: Environmental Effects On Periphyton Compositionsupporting
confidence: 86%
“…Moreover, the periphyton community, which prefers warm water, exhibited higher relative abundances in spring/summer, such as functional groups B, J, and F (Jiang et al, 2013), whereas functional group D which prefers cold water (Jiang et al, 2013), showed higher proportions of periphyton in winter. Our results, therefore, support the view that functional group can be used as an approach to analyze the seasonal variability in algal community (Yang et al, 2011;Yu et al, 2012). Except for winter, the periphyton functional composition responded strongly to nutrient addition and temperature increase, which is consistent with the responses of periphyton genus composition to nutrient and temperature in spring, summer and winter.…”
Section: Environmental Effects On Periphyton Compositionsupporting
confidence: 86%
“…We investigated 17 phytoplankton functional groups according to Padisák et al (2009), and the number was more than that collected in Mudanjiang River (11 FGs) which located in the same province (Yu et al, 2012). Yu et al (2012) also reported that, the distribution of phytoplankton functional groups was significantly affected by tourism. The finding of Tian et al (2015) revealed that phytoplankton community structure was influenced by hydrologic regime, and the water flushed bare riparian zone constantly in Hongze Lake, China.…”
Section: Driving Factors Of Phytoplankton Functional Groupsmentioning
confidence: 96%
“…Geographically, the Muling River is located in northeast China and the light intensity varies with seasons (Yu et al, 2012). We investigated 17 phytoplankton functional groups according to Padisák et al (2009), and the number was more than that collected in Mudanjiang River (11 FGs) which located in the same province (Yu et al, 2012). Yu et al (2012) also reported that, the distribution of phytoplankton functional groups was significantly affected by tourism.…”
Section: Driving Factors Of Phytoplankton Functional Groupsmentioning
confidence: 96%
See 1 more Smart Citation
“…Global alkaline lakes tends to occur in semi-arid or arid areas with very high productivity compared to other aquatic systems (Melack and Kilham 1974;Oduor and Schagerl 2007a) and a confined diversity of microbial life due to high salinity and pH values (Nielsen 1999;Oren 2011). In spite of their ecological value, studies on the composition and distribution of plankton species is very scant compared to freshwater systems (Sun et al 2009;Xu et al 2010;Niu et al 2011;Yu et al 2012;Sui et al 2016). Several environmental factors such as water temperature, conductivity, total phosphorus, calcium ions, magnesium ions and hydrological pattern have been considered as essential factors responsible for shaping biological composition in saline-alkaline lake (Wood and Talling 1988;Oduor and Schagerl 2007b;Schagerl and Oduor 2008).…”
Section: Introductionmentioning
confidence: 99%